Peningkatan Keterampilan Analisis dan Kolaborasi Siswa Dalam Menulis Teks Berita Dengan Metode Teams Games Tournament (TGT) - Azis, Andi Radinal; Ni Nengan Wirjani (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to improve students' analytical and collaborative skills in writing news texts by applying the Teams Games Tournaments (TGT) method. This study uses the Classroom Action Research method with two cycles, involving 36 students from class XI of SMA Negeri 1 Gowa as research subjects. Data were collected through observation, field notes, analysis tests, collaboration tests, and questionnaires. The results of the study showed a significant improvement in students' skills in understanding the elements of news texts (5W+1H), the appropriate use of language, as well as motivation and cooperation within groups. In the first cycle, the average score for students' analytical and collaborative skills reached 71.8%, and increased to 87% in the second cycle. These findings indicate that the application of the Teams Games Tournaments (TGT) learning method is effective in increasing students' active participation, improving the quality of group discussion outcomes, and encouraging students to be more motivated and engaged in learning. Therefore, the Teams Games Tournaments (TGT) method can be an effective alternative in news text learning at senior high schools.